EVOLVING PERSPECTIVES ON CAPITAL STRUCTURE AND FIRM VALUE: A CONCEPTUAL REVIEW WITH REFERENCE TO EMERGING MARKETS - Kansal, Ayush; Sharma, Swati Oza (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Capital structure remains one of the most enduring debates in corporate finance, as firms continuously attempt to identify financing strategies that balance risk, return, and shareholder value. While classical theories such as the Modigliani–Miller irrelevance hypothesis, trade-off theory, and pecking order theory have laid the foundations of capital structure research, empirical evidence—particularly from emerging markets—has often diverged from theoretical predictions. This conceptual paper synthesizes literature from 1958 to 2024, highlighting the evolving perspectives on the relationship between capital structure and firm value, with special reference to emerging economies such as India, Brazil, China, and South Africa. Unlike sector-specific empirical studies, this paper adopts a bibliographic approach, integrating theoretical, empirical, and contemporary debates. The findings emphasize that capital structure–firm value relationships are non-linear, context-dependent, and moderated by factors such as corporate governance, institutional quality, and environmental, social, and governance (ESG) practices. A conceptual framework is proposed to integrate classical theories with contemporary realities, offering a roadmap for future empirical research. The paper contributes to both theory and practice by highlighting how managers, investors, and policymakers in emerging markets can optimize financing decisions to maximize long-term value.